In vitro Antibacterial study of two commonly used medicinal plants in Ayurveda Neem Azadirachta indica L and Tulsi Ocimum sanctum L - Rathod, Gajendrasinh P (International Journal of Pharmaceutical & Biological Archive, 2012)
In vitro Antibacterial study of two commonly used medicinal plants in Ayurveda Neem Azadirachta indica L and Tulsi Ocimum sanctum L